Secure Teleoperation Control Using Somewhat Homomorphic Encryption. Issue 37 (2022) - Kosieradzki, Shane; Zhao, Xiaofeng; Kawase, Hiroaki; Qiu, Yingxin; Kogiso, Kiminao; Ueda, Jun
Abstract: The goal of this research is to establish control theoretic methods to enhance cyber security of networked motion control systems by utilizing somewhat homomorphic encryption. The proposed approach will encrypt the entire motion control schemes including: sensor signals, model parameters, feedback gains, and performs computation in the ciphertext space to generate motion commands to servo systems without a security hole. The paper will discuss implementation of encrypted bilateral teleoperation control schemes with nonlinear friction compensation. The paper will present (1) encrypted teleoperation control realization with somewhat homomorphic encryption and (2) simulation results.